Airport partial and full privatization in a multi-airport region: Focus on pricing and capacity. (May 2015) - Noruzoliaee, Mohamadhossein; Zou, Bo; Zhang, Anming
Highlights: We study airport capacity and pricing in a two-airport region with privatization. After privatization, the privatized airport tends to deviate service price upwards. After privatization, the remaining public airport tends to decrease service price. Under simultaneous decisions, airports have the same capacity investment rule. Airports set capacity differently with sequential decisions. Abstract: This paper studies the capacity and pricing choice of two congestible airports in a multi-airport metropolitan region, under transition from a pure public, centralized airport system to partial or full privatization. We develop analytical models to investigate three privatization scenarios: public–private duopoly, private–private duopoly, and private monopoly. We find that, airports follow the same capacity investment rule as prior to privatization when capacity and pricing decisions are made simultaneously. Pricing rule after privatization becomes more complicated, with additional factors having an upward effect on the privatized airport(s) and a downward effect on the remaining public airport.